Initial Surgical Experience with Aortic Valve Repair: Clinical and Echocardiographic Results - Costa,Francisco Diniz Affonso da (2016)
Abstract Introduction: Due to late complications associated with the use of conventional prosthetic heart valves, several centers have advocated aortic valve repair and/or valve sparing aortic root replacement for patients with aortic valve insufficiency, in order to enhance late survival and minimize adverse postoperative events. Methods: From March/2012 thru March 2015, 37 patients consecutively underwent conservative operations of the aortic valve and/or aortic root. Mean age was 48±16 years and 81% were males. The aortic valve was bicuspid in 54% and tricuspid in the remaining. All were operated with the aid of intraoperative transesophageal echocardiography. Surgical techniques consisted of replacing the aortic root with a Dacron graft whenever it was dilated or aneurysmatic, using either the remodeling or the reimplantation technique, besides correcting leaflet prolapse when present. Patients were sequentially evaluated with clinical and echocardiographic studies and mean follow-up time was 16±5 months. Results: Thirty-day mortality was 2.7%. In addition there were two late deaths, with late survival being 85% (CI 95% - 68%-95%) at two years. Two patients were reoperated due to primary structural valve failure. Freedom from reoperation or from primary structural valve failure was 90% (CI 95% - 66%-97%) and 91% (CI 95% - 69%-97%) at 2 years, respectively. During clinical follow-up up to 3 years, there were no cases of thromboembolism, hemorrhage or endocarditis. Conclusions: Although this represents an initial series, these data demonstrates that aortic valve repair and/or valve sparing aortic root surgery can be performed with satisfactory immediate and short-term results.